PERBANDINGAN PERSEPSI PELAJAR TERHADAP PENGGUNAAN LABORATORIUM KOMPUTER YANG BERBEDA PENGATURANNYA - Nurizah Salleh; Ahmad Fauzi Mohd Ayub; orhasni Zainal Abiddin (Sainteks, 2010)
One of the important elements in the process of teaching and learning is through the usage of computer labs. This computer lab is normally used by students taking computer-based courses. Almost every faculty in the Higher Education Institutions has their own computer labs for their students’ usage. Therefore, it is important that the lab be designed to fit the purpose of the lab and the students as well. The purpose of this study is to identify the students’ perception towards the computer lab environment, teaching style and the similarity of level of inputs received by the students either in the pair arrangement lab and pod arrangement lab. 115 students were involved in this study. The statistic analysis shows that there are significant differences in the mean of lab environment for pair arrangement lab (t(113) = 2.704, p= .008), mean of teaching style (t(113) = 2.159, p=.033) and mean of similarity of level of inputs received (t(113) = 2.88, p = .005) compared to the pod labs. This study implies that lab computers with different structures does result to an environment of more conducive, lecturers’ teaching style and similarity of level of inputs received. Keyword : pair arrangement lab, pod arrangement lab, computer lab environment, teaching styles, similarity